An approach to unifie the axiomatization method of linear values in game theory - Sánchez Sánchez, Francisco (Estudios Económicos de El Colegio de México, 1994)
In the literature of game theory there are several axiomatization of values for games in a characteristic form, each in a particular context. In this work, we present the axiomatization of several values under the same framework. We used the fact that if a lineal operator is defined in a base, it can be extended in a unique form to the whole space, in order to generate several solution's concepts. It is just varying the set of axioms that determine the solution in the base.